Cloning, expression, and purification of the hemolysin/cytolysin (HlyE antigen) from Salmonella enterica serovar Typhi: potential application for immunoassay development - Ong, EBB; Anthony, AA; Ismail, A; Ismail, A; Lim, TS (Elsevier Science Inc, 2024)
Indexed by WOS/ Scopus